"We Think About Our Children First": Asian Skilled Professionals, Liberal Multiculturalism and the Borders of Educational Inequality in Fremont, California. Issue 1 (2nd January 2022) - Chung, Brian Su-Jen
ABSTRACT: This essay examines how the suburban built environment of affluent skilled professionals shaped the political claims that affluent Asian parents made as suburban residents during the 1990 to the early 2000s. In focusing on the school boundary debates and redistribution of educational resources in the Silicon Valley suburb of Fremont, California, I critically unpack how Asian parents advocated for liberal multiculturalism and racial segregation in protecting their access to Fremont's best schools. In contrast to the conception that liberal multiculturalism is a form of resistance to suburban white cultural dominance in school settings, I argue that there are ideological consistencies between suburban homeowner politics of self-interest and Asian parent demands for cultural autonomy. I show how suburban homeowner politics compelled Asian parents to distance themselves from addressing the educational needs of low-income and working-class whites and people of color in Fremont.